DEVELOPMENT OF PERISAI DIRI DIGITAL COMICS BASED ON SIRI' NA PACCE CULTURE TO PREVENT HARASSMENT - Fatimah Azzahrah Ayu; Abdullah Sinring; Suciani Latief (Jurnal Konseling Pendidikan Islam, 2026)
Study aims to develop the “Perisai Diri” digital comic, based on the Siri’ Na Pacce cultural values, to prevent sexual harassment among students at UPT SPF SMP Negeri 5 Makassar. Sexual harassment is any form of sexually connotative act carried out without the consent of the other party or through coercion. Therefore, there is a need for effective information service media that can deliver educational messages to both victims and potential perpetrators, incorporating strong local cultural values in an engaging format. The main focus of this study includes four aspects: (1) identifying the needs for developing the “Perisai Diri” digital comic based on Siri’ Na Pacce culture, (2) designing the prototype of the comic, (3) assessing the validity of the media, and (4) assessing the practicality of the media. The research employed a modified Borg & Gall development model, consisting of seven stages: preliminary study, initial design planning, prototype development, expert validation, product revision, limited trials, and refinement. Data were collected through questionnaires, expert validation sheets, and instruments for measuring practicality and effectiveness. The findings show that the “Perisai Diri” digital comic is considered highly necessary and relevant by students and guidance counselors. The media proved effective and practical in supporting digital guidance and counseling services. Therefore, the “Perisai Diri” digital comic is recommended as an innovative medium that can effectively address students’ needs, particularly in preventing sexual harassment.